Anthropometric characteristics of top-class world and European male table tennis players - Djokic, Z.; Munivrana, G.; Levajac, D. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The purpose of this study was to compare anthropometric profiles of top 100 ITTF Rank male table tennis players and to set up a set of reference values useful for future investigations on athlete selection, talent identification, and training programme development. Methods: Seventy-five best world players, ranked in the top 100 at the ITTF Rank list (male) were analysed. The following data were taken: Body high, Body weight, Body mass index, age, Continent affiliation and playing hand. Players were distributed in groups according to performance level. Descriptive statistics parameters were calculated for all analysed players according their performance level. Differences between groups (performance level, Asian and European players, Right-handed vs. left-handed; different age categories) were analysed with One-way ANOVA test (p<.05). Results: Anthropometric characteristics of best World players were: Body high: 180.0±6.8 cm, Body weight: 73.99±7.93 kg, Body mass index: 22.80±1.81 and Age: 29.3±5.6. Asian players have: Body high: 175.0±5.3 cm, Body weight: 68.57±6.49 kg, Body mass index: 22.36±1.84 and Age: 27.4±4.3 and European players: Body high 183.9±5.6 cm, Body weight 76.70±6.5 kg, Body mass index 22.96±1.74 and Age 30.5±6.1 years old. Results of ANOVA showed that there are no statistical significant differences in anthropometric characteristics according performance level, while that there is in Body high and Body weight between continental affiliations. These reference data should be useful to practitioners and researchers, providing useful information for talent identification establishing the model of top table tennis player and development for the assessment of training progression in table tennis.